The relationship between measures of cycle intensity and running economy - Bonacci, J.; Blanch, P.; Saunders, P.; Green, D.; Vicenzino, B. (Journal of Science and Medicine in Sport, 2011)
Introduction: Triathlon success depends primarily on a triathlete`s ability to run efficiently after cycling. Running economy is influenced by the preceding cycle and previous investigations have reported variable changes in running economy after cycling in triathletes. However, there is little information on what measures of cycle intensity are related to subsequent running economy. Purpose: To determine which commonly measured variables of cycling intensity are related to subsequent running economy. Methods: Running economy was compared between a control run (no preceding cycle) and a run performed after a 45 min high intensity cycle in eighteen triathletes. Cycling intensity was monitored throughout the cycle using power output, heart rate, rating of perceived exertion (RPE) and blood lactate concentration. The relationship between these measures of cycle intensity and the change in running economy was evaluated using pearson`s correlation. Changes in running economy were also interpreted using the smallest worthwhile change (> 2.4%) and grouped accordingly (i.e. impaired, no change or improved running economy). The differences in cycle intensity between groups were evaluated using a one-way analysis of variance and Tukey`s post hoc test. Results: Triathletes` RPE at the end of the cycling bout was significantly associated with the change in running economy after cycling (r = 0.57, p = 0.01). Average RPE of the cycling bout and RPE at the end of the cycling bout were also significantly different between groups (p = 0.04 and 0.02 respectively). Post hoc tests revealed that average RPE and RPE and the end of the cycling bout were significantly different between the impaired and improved running economy groups, with increases in RPE scores being related to impairments in running economy (p = 0.04, standardized mean difference = 2.5 and p = 0.02, standardized mean difference = 2.8, respectively). None of the other variables of cycle intensity were associated with the change in running economy after cycling. Conclusions: RPE during cycling is associated with subsequent running economy in triathletes. RPE is a simple, cost-effective measure that triathletes and their coaches can use in competition and training to control cycling intensity without the need for specialised equipment such as crank systems or blood analyzers.